Urgensi Penarikan Pajak Penghasilan Profesi Youtuber dan Selebgram Sebagai Upaya Mendorong Stabilisasi Perekonomian Pasca Pandemi - Arty sriwahyuni Br Perangin Angin; Helena Helen Hestaria Lumban Gaol (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic has almost paralyzed all economic activities in Indonesia. In the current era of the Industrial Revolution 4.0, Selebgram and Youtubers are new professions that were never thought of 20 years ago. The era of social media creates millions of new jobs. Celebgram and YouTuber are professions that are very developing nowadays so that the demand is increasing every year. Because the interest in this profession is getting higher because the income is quite promising so that it meets the requirements to be a tax object, of course the government has followed up on this by issuing regulations related to income tax on the profession of celebrities and YouTubers. The legal basis that regulates taxes for celebrities and YouTubers is regulated in Law Number 16 of 2009 concerning General Provisions and Tax Procedures. This is an attempt by the government to accelerate the increase in Indonesian income by boosting tax revenue. However, there is still a lack of awareness among programmers and YouTubers in paying taxes, so it is important for the government to socialize to taxpayers about general provisions and procedures for carrying out tax payment obligations to increase tax revenue and state revenue for a more stable state economy. The purpose of this research is to find out and analyze the effectiveness of tax imposition for the celebgram and YouTuber profession, as well as the application of Law Number 36 of 2008 concerning Income Tax in overcoming the barriers faced by celebrities and YouTubers in implementing the application of income tax. The method in this research is qualitative, research that emphasizes the meaning, reasoning, definition of a particular situation, and researches more on relevant literature and areas of daily life to obtain descriptive data.